Pediatric Ent Pathology Cases in Hospitals - Deing Dioalla (Journal La Medihealtico, 2022)
Very few studies have been conducted in the ENT profession that did not include the use of an ENT expert. For this cross-sectional study, we sought to determine the level of activity in the pediatric ear, nose, and throat department. This was a prospective, cross-sectional research including ENT functional unit patients who had been observed for a period of time. A patient's age ranged from 7 months to 180 months during a consultation. A sex ratio of 1.2 (61/51) was recorded. With 33.5 percent of the patients, pharyngolaryngeal disease was followed by otological, rhinological, and other pathologies with 30 percent and 26.88 percent, respectively. Pediatric ENT has a significant role in the field of ENT. As a result of our research, we were able to demonstrate the wide range of services available in pediatric ENT pathology in remote areas. It is clear that these findings support the idea of distributing specialist services more widely. As a result of these findings, it is recommended that ENT services be decentralized in order to better serve this vital segment of the population.